Effect of the Timing Addition of Ferrosilicon with Al and Ca Impurities on Inclusion Formation in Al‐Killed Automobile Gear Steel SCr420H. Issue 1 (26th August 2022) - Sun, Meng; Jiang, Zhouhua; Li, Yang; Li, Huabing; Chen, Changyong; Ma, Shuai; Ji, Yongshuai; Wang, Ju; Ma, Yanshuo
Abstract : The current study investigates the effect of the timing of the addition of ferrosilicon with Al and Ca impurities on the inclusion evolution during the refining process of Al‐killed gear steel SCr420H. To achieve this aim, laboratory experiments and thermodynamic calculations are conducted. The process sample, the ingot sample, and ferrosilicon are polished and analyzed by scanning electron microscope‐energy dispersive spectrometer. The results show that Ca and Al impurities mainly exist as intermetallic compounds or are segregated on the phase boundary between FeSi2 and Si in the ferrosilicon. The Ca content of the ingot increased with the delay of adding the ferrosilicon with Al and Ca impurities. In case the ferrosilicon is added at the end of the refining process, many liquid calcium aluminate inclusions can be observed in the ingot, which indicates that changing the timing of adding ferrosilicon with Al and Ca impurities is a promising way to modify inclusion to liquid inclusion. Based on the thermodynamic calculation, MgO‐saturated spinel is more easily modified into CaO–Al2 O3 inclusion than spinel with low MgO content. When ferrosilicon is added in steel containing enough Mg, inclusions are transformed into spinel with high MgO content first, and afterward are modified into liquid calcium aluminate inclusions. Abstract : Experiments with different adding timing of ferrosilicon with Al and Ca impurities are carried out. It is found that when ferrosilicon is added at the end of the refining process, many liquid inclusions can be observed in the ingot, which indicates that changing the timing of adding ferrosilicon with impurities is a promising way to modify inclusion.